Next‐generation phylogeography of the cockle Cerastoderma glaucum: Highly heterogeneous genetic differentiation in a lagoon species. Issue 8 (27th March 2019) - Sromek, Ludmila; Forcioli, Didier; Lasota, Rafal; Furla, Paola; Wolowicz, Maciej
Abstract: Aim: Coastal lagoons form an intriguing example of fragmented marine habitats. Restricted gene flow among isolated populations of lagoon species may promote their genetic divergence and may thus provide a first step toward speciation. In the present study, the population genetic structure of the lagoon cockle Cerastoderma glaucum has been investigated to clarify the complex phylogeographic pattern found in previous studies, to localize major genetic breaks, and to discuss their origin and maintenance. Location: The Atlantic and Mediterranean coasts, including the Baltic, North Sea, and Black Sea. Methods: A total of 204 C. glaucum individuals from 14 populations were genotyped using restriction site‐associated DNA sequencing (RADseq). The genetic diversity, divergence, and structure were analyzed using genome‐wide single nucleotide polymorphisms (SNPs). Phylogenetic relationships were inferred under a coalescent model usingSVDquartets . Results: The RADseq approach allowed inferring phylogeographic relationships with an unprecedented resolution. Three deeply divergent lineages were identified within C. glaucum that are separated by many genetic barriers: one lineage in the Aegean–Black Sea region, one in the Ionian Sea, and the last one widely distributed from the Western Mediterranean to the Baltic Sea. The nested branching pattern displayed on the species tree largely agrees with the likely scenario of C. glaucum postglacial expansion from the Mediterranean to the Baltic Sea. Main conclusion: The genetic differentiations between geographically separated lagoons proved to be strong, highlighting the evolutionary influence of these naturally fragmented habitats. The postglacial expansion created complex patterns of spatial segregation of genetic diversity with allele frequency gradients in many outlier loci, but also discrepancies between the nuclear and mitochondrial genetic markers that probably arose from genetic surfing of mitochondrial variation. Abstract : In the present study, the genetic population structure of the lagoon cockle Cerastoderma glaucum has been studied using restriction site‐associated DNA sequencing (RADseq). The genetic differentiations between geographically separated lagoons proved to be strong, highlighting the evolutionary influence of these naturally fragmented habitats. The postglacial expansion created complex patterns of spatial segregation of genetic diversity with allele frequency gradients in many outlier loci, but also discrepancies between the nuclear and mitochondrial genetic markers that probably arose from genetic surfing of mitochondrial variation.